The role of two sediment-dwelling invertebrates on the mercury transfer from sediments to the estuarine trophic web - Coelho, J. P. (2008)
The annual total and organic mercury bioaccumulation pattern of Scrobicularia plana and Hediste diversicolor was assessed to evaluate the potential mercury transfer from contaminated sediments to estuarine food webs. S. plana was found to accumulate more total and organic mercury than H. diversicolor, up to 0.79 mg kg-1 and 0.15 mg kg-1 (wet weight) respectively, with a maximum annual uptake of 0.21 mg kg-1 y-1, while for methylmercury the annual accumulation was similar between species and never exceeded 0.045 mg kg-1 y-1. The higher organic mercury fraction in H. diversicolor is related to the omnivorous diet of this species. Both species increase methylmercury exposure by burrowing activities and uptake in anoxic, methylmercury rich sediment layers. Integration with the annual biological production of each species revealed mercury incorporation rates that reached 28 [mu]g m-2 y-1, and to extract as much as 11.5 g Hg y-1 (of which 95% associated with S. plana) in the 0.4 km2 of the most contaminated area, that can be transferred to higher trophic levels. S. plana is therefore an essential vector in the mercury biomagnification processes, through uptake from contaminated sediments and, by predation, to transfer it to economically important and exploited estuarine species.